2017
DOI: 10.1002/jcla.22128
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for kaolin‐activated thromboelastography in volunteers of Anhui Province in China

Abstract: This study established the reference values for kaolin-activated TEG in the target Chinese population, which might provide a reference for both clinical and laboratory studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…Our results showed that the specificity of the normal reference range provided by the manufacturer was 79.7% in the local healthy population, agreed with the results by Scarpelini et al (6). In addition, similar to other studies (16, 17), we found that the females had stronger coagulation function and a greater proportion of females were in hypercoagulable state as compared with males. We also detected the influence of age on TEG.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that the specificity of the normal reference range provided by the manufacturer was 79.7% in the local healthy population, agreed with the results by Scarpelini et al (6). In addition, similar to other studies (16, 17), we found that the females had stronger coagulation function and a greater proportion of females were in hypercoagulable state as compared with males. We also detected the influence of age on TEG.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, comparison between the RIs established by our study with indirect method and the RIs proposed by manufacturer was conducted. Similar to those reported by others,[23][24][25] the RIs from manufacturer's recommendation was basically not in agreement with those determined by our study in all parameters except of K, but diagnostic specificity was relative high with consistent percentage of 75.3, 91.8, 80.4, 87.7, 95.2, and 92.5 for R, K, αAngle, MA, LY30, and CI, respectively. Nevertheless, it still supports the recommendation of manufacture that each laboratory should determine its own RIs of TEG before adopting this test in clinical application.…”
supporting
confidence: 76%
“…It was suggested that gender and age would influence on TEG values, we performed comparisons of the results of all measured TEG parameters by stratification based on gender, age, and gender-specific age. [23][24][25]37 In our population, female presented statistically more hypercoagulablity than male population in all parameters, which was well consistent with the study that also included Chinese participants 25 ; but there was no agreement with the study of Subramanian et al, 23 which showed no significant difference in all TEG parameters between male and female with only MA showing higher in female but none of statistical significance being found; in the other studies on the RIs of TEG, they reported the similar higher coagulation ability in female as our findings, but with the exception of R value being absent of statistical difference between genders. 24,37 These discrepancies might be possibly explained by different device used by Subramanian et al 23 and different ethnic population enrolled by others.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early HAT occurred in 23 (2.7%) patients; AUC for preoperative MA>65mm was 0.75 and for preoperative platelet count>145 cells/ cubic mm was 0.71. However, these cutoffs were determined post-hoc based upon the 75 th percentile values in patients that did not develop HAT and do not reflect the upper limit of normal for kTEG MA (33,34).…”
Section: Prediction Of Post-operative Thrombotic Complications In LIVmentioning
confidence: 99%